The Impact of Dependence on Gadgets on Student Concentration and Academic Performance - Baso Intang Sappaile (Journal Emerging Technologies in Education, 2024)
Background:One impact that can disrupt students' concentration in studying is gadget dependence. This dependency can have an impact on students' academic achievement, such as decreasing test scores and poor learning quality and achievement. Therefore, schools must better monitor students' use of gadgets during lessons at school and notify students' parents or guardians to supervise or limit students' use of gadgets at home. Research purposes:This research was conducted with the aim of understanding the relationship between the impact of dependence on gadgets on students' learning concentration and academic performance, as well as the extent of the impact of dependence on gadgets on students. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From this research, researchers were able to obtain research results on the impact of dependence on gadgets on students' learning concentration and academic performance, which can indeed have a very big influence on students' focus in learning. However, if the use of gadgets can be utilized properly, the resulting negative impact on students' concentration and academic performance will be less. Conclusion:Based on the results of this research, it can be concluded that the impact of dependence on gadgets, if used frequently, will have an impact on students' learning concentration. By decreasing student concentration in learning, it can result in fatalities such as decreasing the level of student achievement itself. Therefore, supervision is needed, especially by parents, so that students at home do not always play or use gadgets all the time.